Proceedings IEEE Workshop on Omnidirectional Vision (Cat. No.PR00704)
DOI: 10.1109/omnvis.2000.853813
|View full text |Cite
|
Sign up to set email alerts
|

Catadioptric sensors that approximate wide-angle perspective projections

Abstract: We present two families of reflective surfaces that are capable of providing a wide field of view, and yet still approximate a perspective projection to a high degree. These surfaces are derived by considering a plane perpendicular to the axis of a surface of revolution and finding the equations governing the distortion of the image of the plane in this surface. We then view this relation as a differential equation and prescribe the distortion term to be linear. By choosing appropriate initial conditions for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 15 publications
0
37
0
2
Order By: Relevance
“…Hicks and Bajcsy as well as Kweon et al showed how to compute mirror shapes such that a particular scene plane that is "frontoparallel" to the mirror is imaged without distortion, while still providing a very wide field of view [222,223,297]. This was done for both, perspective and orthographic cameras looking at the mirror.…”
Section: Non-central Catadioptric Camerasmentioning
confidence: 99%
“…Hicks and Bajcsy as well as Kweon et al showed how to compute mirror shapes such that a particular scene plane that is "frontoparallel" to the mirror is imaged without distortion, while still providing a very wide field of view [222,223,297]. This was done for both, perspective and orthographic cameras looking at the mirror.…”
Section: Non-central Catadioptric Camerasmentioning
confidence: 99%
“…한편 카메라와 부가적인 반사체를 혼합하여 영상을 획득하는 것을 catadioptric(catoptric + dioptric) 방법이라고 한다 [10]. Catadioptric 시스템은 한 대의 카메라를 통해 여러 시점의 영상을 획득하거나 [7,8] …”
Section: 서론unclassified
“…However, a big problem of today's catadioptric systems is their focusing as this is not considered during system design. Instead common designs only deal with the geometric mapping that describes the relation between image points and corresponding lines of sight (Hicks and Bajcsy, 2000;Stürzl and Srinivasan, 2010). Neglecting wave effects, the light transport through an optical system can be described using light rays (Malacara and Malacara, 2003).…”
Section: Introductionmentioning
confidence: 99%